Don’t Rich People Difficult: Bilingual Puns on Indonesian Truck Graffiti - Norwanto Norwanto; Bahroni Bahroni (Journal of Pragmatics Research, 2023)
Most studies discussed puns in a single language or in a code-switching, which can be understood in the language. This study analyzed different puns, in which the readers can only understand the intention of humour in a different language. It aims to determine the types of bilingual puns, the forms and how to interpret them. It is a qualitative study, and the data were obtained through field and virtual observation. This study found two different types of bilingual puns: English-Indonesian puns (EIPs) and English-Javanese language puns (EJLPs). The puns were written in English but the meaning can only be understood in Bahasa Indonesia or Javanese language. The analysis also showed EIPs and EJLPs are bilingual puns comprising colloquial languages of Indonesian people rewritten in English. Syntactically, both are composed of ungrammatical English word orders with the syntactic forms reflected in Indonesian (BI) or Javanese (JL) languages. The interpretation processes involve word-to-word translation and sound pairing translations. The first technique typically involves: EIPs/EJLPs – word-to-word translation – ambiguity. The second way involves: EIPs/EJLPs – sound pairing translation – sound ambiguity/similarity.